Hypertrophied myocardium is more dependent on extracellular calcium than the normal cardiac muscle - de Barros, Reginaldo [UNESP]; Zornoff, Leonardo A. M. [UNESP]; Ribeiro, Henrique B. [UNESP]; Okoshi, Marina P. [UNESP]; Padovani, Carlos R. [UNESP]; Aragon, Flávio F. [UNESP]; Cicogna, Antonio C. [UNESP] (My University, 2010)
Background: The aim of this study was to analyze stable hypertrophied myocardial function and its response to inotropic maneuvers in rats submitted to renovascular hypertension for a 10-week period (RHT group, n=10). Material/Methods: Myocardial performance was studied in isolated left ventricle papillary muscles in isometric contraction under the following conditions: at postrest contraction of 30 seconds (PRC), at extracellular calcium (ECa2+) chloride concentration of 1.25 and 5.20 mM, and after beta-adrenergic stimulation with 10-6 M isoproterenol (ISOP). Results: The results were compared with normotensive Wistar controls rats (C group, n=10). In basal condition, resting tension, and contraction time (TPT) were greater, while relaxation time (RT50) tended to be longer in RHT than C group. PRC and ISOP promoted a similar change in muscle function response intensity (Δ) in both groups. ECa2+ shift did not change TPT in the C group and decreased TPT in the RHT animals; Δ was different between these groups. RT50 increased in C and decreased in RHT, both without statistical significance; however, Δ was different. Conclusions: These results suggest that hypertrophied myocardial dysfunction may be attibuted to changes in intracellular calcium cycling. © Med Sci Monit, 2010.
Keywords: Calcium isoproterenol; Myocardium function; Papillary muscle; Renovascular hypertension